On p-robust saturation for hp-AFEM. (1st May 2017) - Canuto, Claudio; Nochetto, Ricardo H.; Stevenson, Rob; Verani, Marco
Abstract: For the Poisson problem in two dimensions, we consider the standard adaptive finite element loop solve, estimate, mark, refine, with estimate being implemented using the p -robust equilibrated flux estimator, and, mark being Dörfler marking. As a refinement strategy we employ p -refinement. We investigate the question by which amount the local polynomial degree on any marked patch has to be incremented in order to achieve a p -independent error reduction. We show that the analysis can be transferred from the patches to a reference triangle, and therein we provide clear-cut computational evidence that any increment proportional to the polynomial degree (for any fixed proportionality constant) yields the desired reduction. The resulting adaptive method can be turned into an instance optimal h p -adaptive method by the addition of a coarsening routine.